Entwicklung von Ansätzen zur Erweiterung der Prozessgrenzen in industrienahen Laborversuchen anhand einer Streifenzuganlage - He, Franz; Merklein, Marion; Dechant, Stefanie (Warmumformung von höchstfesten Vergütungsstählen: Tagungsband zum 17. Erlanger Workshop Warmblechumformung, 2022)
Zur Umsetzung der immer weiter steigenden Anforderungen an die passive Sicherheit bei gleichzeitiger Verringerung des Bauteilgewichts spielt die Warmumformung ein wesentliche Rolle. Die Technologie des Presshärtens bietet dabei die Möglichkeit zur Herstellung höchstfester Strukturbauteile bei gleichzeitig reduzierter Wandstärke. Um Verzunderung zu unterbinden und Korrosionsschutz im Prozess zu gewährleisten, wird auf die verwendeten Blechhalbzeuge eine Aluminisum-Silizium(AlSi)-Beschichtung aufgebracht. Die Werkstück-beschichtung wurde als Hauptursache für die adhäsive Verschleißbildung identifiziert und hat somit einen entscheidenden Einfluss auf die Werkzeugstandzeit und die Qualität von pressgehärteten Bauteilen. Die Entwicklung effektiver Maßnahmen zur Verringerung von Reibung und Verschleiß setzt ein grundlegendes Prozessverständnis in Bezug auf das tribologische System voraus. Vor diesem Hintergrund werden die industriellen Presshärtebedingungen im Labormaßstab anhand von Streifenzuganlagen abgebildet. Ein limitierender Faktor im Flachbahnzugversuch in bisherigen Untersuchungen ist die erreichbare Flächenpressung. Während die existierende Anlage eine theoretische maximale Flächenpressung von 130 MPa umsetzen kann, können bereits Anpressdrücke von 7,5 MPa zur Ausbildung von Kaltverschweißungen durch Abscherung der Beschichtung und Reibzahlabbrüchen führen. Vor diesem Hintergrund werden Störfaktoren im Versuch identifiziert, um die vorhandene Warmstreifenziehanlage zu modifizieren und Versuche unter industrierelevanten Parametern durchzuführen. <
Keywords: Streifenzugversuch; Reibkoeffizient; Verschleiß; 22MnB5

Erarbeitung einer Methodik zur Abbildung tribologischer Bedingungen im Presshärteprozess unter Verwendung einer Warmstreifenziehanlage mit Umlenkung - He, Franz; Harms, Arnold; Merklein, Marion (Tagungsband zum 19. Erlanger Workshop Warmblechumformung 2024, 2024)
Im Automobilbereich hat sich das Presshärten als Herstellungsverfahren für sicherheitskritische Komponenten in der Karosserie wie der B-Säule etabliert. Durch die Austenitisierung des Bor-Mangan-Stahls bei Temperaturen über Ac3 kann die Maßhaltigkeit gesteigert und die Rückfederung gesteigert werden, wenn bei hohen Temperaturen umgeformt wird. Der Kontakt mit dem gekühlten Werkzeug löst zusätzlich eine Martensithärtung aus, wodurch das finale Bauteil bei Raumtemperaturen gute mechanischen Eigenschaften und insbesondere hohe Festigkeiten aufweist. Aufgrund der hohen Temperaturen ist ein Einsatz von Schmierstoffen bisher nicht möglich. Um die auftretenden tribologischen Eigenschaften zu untersuchen werden bisher Laborversuche über eine flache Ebene genutzt, die die Kontaktbedingungen im Flanschbereich wiedergeben. Da sich der kritische Bereich der Ausdünnung und Verschleißentstehung im Bauteil auf die Kontaktzone im Matrizeneinlaufradius konzentriert, wurde mit dem Streifenzug mit Umlenkung ein neuer Versuchsprüfstand adaptiert, um die Verhältnisse in der Wirkfuge am Werkzeugradius wiedergeben zu können.<br
Keywords: Presshärten; Tribologie; Umlenkung; 22MnB5; Aluminium-Silizium

Investigation of the impact of heat treatment on the layer formation of AlSi-coated boron-manganese steel - He, Franz; Merklein, Marion (INTERNATIONAL DEEP-DRAWING RESEARCH GROUP CONFERENCE (IDDRG 2021), 2021)
Hot stamping is a well-established technology for producing safety relevant car components. The usage of hot stamping allows for reduced sheet thicknesses and weight of formed parts due to an increase in strength because of martensitic phase transformations. To prevent surface carburization and the formation of oxide layers AlSi coatings are applied to the workpiece surface. Due to a lack of suitable lubricants at process temperatures of over 800 °C, severe friction and wear affect the final part quality. Furthermore, process temperatures influence the layer formation and surface roughness due to diffusion processes. Consequently, a deeper process understanding is needed to acquire detailed knowledge of the impact on the tribological behavior to increase part quality and reduce tool wear. To this end the influence of heat treatment parameters on the coating layer and the subsequent layer formation is analyzed by comparing the resulting material composition and surface roughness. This is achieved by analyzing the impact of the furnace temperature and holding time on an AS150 coating and determining the effect of the parameters via metallographic investigation and tactile measuremen
CRIS-Team WoS Importer:2021-11-05

Investigation of the impact of process parameters on the layer formation of AlSi coated boron-manganese steel - He, Franz; Merklein, Marion (International Deep-Drawing Research Group Conference (IDDRG 2022), 2022)
Hot stamping has established itself as a technology for manufacturing safety-relevant car body components. Its usage has found increased importance due to rising political and social pressure e.g. for improved fuel conservation. Due to reduced sheet thickness, hot stamping parts offer lightweight solutions while at the same time providing improved crash performance due to their high strength. Boron-manganese steel is commonly used in hot stamping processes. Due to hot scale formation during heat treatment and the subsequent forming process, additional coatings, typically AlSi-coatings, are applied. Since hot stamped parts are formed at temperatures of 600 °C to 800 °C no suitable lubricants have yet been found. This leads to increased friction and severe wear in the process, which negatively affect tool lifetime and overall part quality. Additionally, process temperatures influence the layer formation and surface roughness due to diffusion processes. A deeper process understanding is needed to acquire detailed knowledge of the resulting impact on tribological behavior. Within this study, the effect of coating thickness on the resulting layer is analyzed by comparing the resulting material composition and surface roughness. To this end, the layer formation and surface roughness are analyzed for two different layer thicknesses (AS150 and AS80) in relation to furnace temperature, holding time and heat up rate. Both are characterized by means of heating experiments conducted on an annealing furnace. The change in layer composition and surface roughness are determined via metallographic investigation and tactile measurement. The results of this study help to improve the process understanding of the tribological conditions within the hot stamping process and to develop future measures for reducing tool we
Keywords: Hot Stamping; 22MnB5; Coating

Investigation of the impact of the layer formation of AlSi coated boron-manganese steel in regard to friction and wear - He, Franz; Merklein, Marion (International Conference on Hot Sheet Metal Forming of High Performance Steel, 2022)
With the increase in electric vehicles, factors for limiting reach due to finite battery capacity have found increased significance. Lightweight solutions are needed, amongst which the construction with ultra-high strength steels have been established as the industrial standard. These materials are able to bridge the gap between providing reduced part weight while improving mechanical properties. While cold forming faces various challenges such as high forming resistance and spring-back behavior, hot stamping of boron manganese steels allow for reduced forming forces and increased dimensional accuracy. The sheet is austenized at temperatures above 850 °C which leads to a phase change in the material and decrease in tensile strength. Since uncoated material suffers from decarburization and scale formation, which negatively inform the forming process and final part quality, aluminum silicon coatings (Al-Si) are applied. Additionally, lubricants lose their properties at higher process temperatures, leading to increased friction and severe wear in the process. Previous investigations have shown that furnace holding times influence the layer formation of AlSi-based coatings due to diffusion processes. Within this study, the influence of furnace holding times and subsequent layer formation on the friction and wear behavior as well as interdependencies with other relevant process parameters is investigated. To this end single sided strip drawing tests are performed with an industrial standard coating AS150 and analyzed in regard to the friction coefficient. Additionally, the tool sided wear is investigated through contactless 3D measurement. The results of this study help to improve the process understanding of the tribological conditions within the hot stamping process and to develop tailored measures for reducing tool wear.
Keywords: Friction; wear; hot stamping; 22MnB5

Investigation of the influence of workpiece-side parameters on the layer formation of zinc-coated boron-manganese steel - He, Franz; Merklein, Marion (Materials Research Proceedings, 2023)
The hot stamping process has been established as a technology for the production of ultrahigh-strength steel parts for safety-relevant components in lightweight construction for the automotive sector. Thanks to the reduced overall thickness combined with high tensile strength, it is possible to realize lightweight design concepts with improved crash behavior. Boron-manganese steels are usually used for this purpose. Due to initial process temperatures above 800 °C, hot stamping is considered a lubricant-free process. In addition to high friction and wear in the process, surface scaling and the need for tool repairs are the result. In light of these phenomena, hot stamping materials are coated to protect them from corrosion. Until now, aluminum-silicon-based coatings have been primarily used for the direct hot stamping route. While zinc-based coatings have so far mainly found usage in the indirect process route, they are now also become a valid alternative for the direct process route. In previous investigations, a significant influence of workpiece-side parameters on the formation of the coating during the austenitization process was found for aluminum-silicon (AlSi) coatings. In light of this, a similarly significant influence is suspected for zinc-based coatings. The parameters heating rate, furnace temperature and dwell time in the furnace and the effect on the coating formation of zinc-coated 20MnB8 during austenitization will be investigated. The resulting findings will form the basis for further experiments to investigate the influence of the parameters on friction and wear in the industry near strip drawing tests.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 20MnB8; Coating; Hot Stamping

Investigation of the Tribological Impact of the Tool Radius on a Strip Drawing Test Rig With Redirection - He, Franz; Merklein, Marion (9th International Conference on Hot Sheet Metal Forming of High-Performance Steel, CHS2 2024 - Proceedings, 2024)
With the rise in electric vehicles, the focus on the reduction in the overall weight of the personalized motorized vehicle provides a central focus point in the automotive industry. Hot stamping has been established as a suitable process for the generation of critical structural components in the body in white which provide improved strength and stiffness at reduced component weight. Due to the high process temperatures suitable lubricants have not yet been found. Direct results are both high friction and occurrences of wear on both tool and workpiece. To characterize the tribological conditions in the hot stamping process flat strip drawing tests have been commonly used. These however only accurately represent the flange area of a workpiece, while the critical sheet thinning can be observed at radii where the additional bending motion changes the contact conditions. To properly reproduce the tribological conditions in the tool radius area an existing strip drawing test rig at the Institute of Manufacturing Technology has been modified to allow for a strip drawing test with redirection. Using the test rig in combination with the results of a simulation of the process allows for an inverse determination of the friction coefficients present. The results of this study help to improve the process understanding of the contact and tribological conditions in the tool radius area in the hot stamping process. Furthermore tailored measures can be developed based on the findings of this study to improve the part quality and overall tool lifetime.
CRIS-Team Scopus Importer:2024-07-19

Untersuchung des Einflusses von werkstückseitigen Parametern auf die Schichtausbildung von zinkbeschichtetem Bor-Manganstahl - He, Franz; Merklein, Marion (Warmumformung von höchstfesten Vergütungsstählen: Tagungsband zum 16. Erlanger Workshop Warmblechumformung, 2021)
Das Presshärteverfahren hat sich als Technologie zur Herstellung von höchstfesten Stahlwerkstoffen für sicherheitsrelevante Bauteile im Karosserieleichtbau etabliert. Durch ihren Einsatz lassen sich aufgrund reduzierter Blechdicke in Kombination mit hohen Zugfestigkeiten Leichtbaukonzepte bei gleichzeitig verbessertem Crashverhalten realisieren. Dabei kommen für gewöhnlich Bor-Mangan-Stähle zum Einsatz. Aufgrund von Prozesstemperaturen über 800 °C gilt das Presshärten als schmierstofffreies Verfahren. Neben hoher Reibung und Verschleiß im Prozess sind Oberflächenverzunderung und Nachbearbeitung die Folge. Zum Schutz vor Korrosion werden Presshärtewerkstoffe deswegen beschichtet. Bisher kamen hauptsächlich Beschichtungen auf Aluminium-Silizium-Basis für das direkte Presshärten zum Einsatz. Während Beschichtungen auf Zink-Basis bisher vorwiegend im indirekten Prozessablauf Anwendung fanden, erschließt sich diese inzwischen auch für die direkte Verfahrensroute. In vorherigen Untersuchungen konnte für Aluminium-Silizium (AlSi) Beschichtungen ein signifikanter Einfluss von werkstückseitigen Parametern auf die Ausbildung der Beschichtung während des Austenitisierungsprozesses festgestellt werden. Vor diesem Hintergrund wird ein ähnlich signifikanter Einfluss für Beschichtungen auf Zink-Basis vermutet. Im Zuge dessen sollen die Parameter Aufheizrate, Ofentemperatur und Ofenverweilzeit und die Auswirkung auf die Schichtausbildung von zinkbeschichteten 20MnB8 während der Austenitisierung untersucht werden. Die sich daraus ergebenden Erkenntnisse bilden die Basis für weiterführende Versuche, um den tiefergehenden Einfluss der Parameter auf Reibung und Verschleiß im industrienahen Streifenzugversuch zu untersuchen. <
Keywords: Zinkbeschichtung; 20MnB8; Direktes Presshärten

Werkstückseitige Beeinflussung und Modellierung der tribologischen Bedingungen beim Presshärten - He, Franz; Merklein, Marion (2022)
Das Auftreten von Reibung und Verschleiß stellt eine akute Herausforderung im Presshärteprozess dar, da aufgrund von erhöhten Prozesstemperaturen > 850 °C der Einsatz von Schmierstoffen nicht möglich ist. Die tribologischen Bedingungen in der Wirkfuge zwischen Werk- und Halbzeug bilden dabei eine kritische Komponente im Prozess, die sowohl die Werkzeugstandzeit als auch finale Produktqualität maßgeblich beeinflusst. Während im vorangegangenem Projekt P1228/19337 „Werkzeugseitige Beeinflussung der tribologischen Bedingungen beim Presshärten“ die werkzeugseitigen Einflussfaktoren auf den Presshärteprozess untersucht wurden, zeigen bisherige Forschungsarbeiten, dass die werkstückseitig eingesetzte Beschichtung im Halbzeug einen maßgeblichen Einfluss auf die auftretenden Reib- und Verschleißmechanismen haben. Die Zielsetzung des Forschungsvorhabens besteht darin, funktionale Wirkzusammenhänge zwischen den Austenitisierungsparametern und der Schichtausbildung sowie dem tribologischen Einsatzverhalten von Beschichtungswerkstoffen beim Presshärten zu ermitteln. Durch das Verständnis der Wirkzusammenhänge werden Maßnahmen abgeleitet, welche die Standzeit von Presshärtewerkzeugen und somit die Wirtschaftlichkeit des Prozesses erhöhen. Um das Forschungsziel zu erreichen, wurden in Absprache mit den Industriepartnern zwei Werkstückwerkstoffe mit unterschiedlichen Beschichtungen für die Untersuchungen ausgewählt. Darüber hinaus wurden unterschiedliche Austenitisierungsparameter und deren Einfluss auf die resultierende Ausbildung der Beschichtung analysiert. Die Ergebnisse dienten dazu, signifikante Parameter zu identifizieren und deren Einfluss auf Reibung und Verschleißverhalten auf Basis des Streifenziehversuchs zu untersuchen. Die Untersuchungen haben gezeigt, dass die Austenitisierungsparameter im Rahmen der Laborversuche keine Auswirkung auf das resultierende Reibverhalten haben. Jedoch kann sowohl die Wahl des Werkstückwerkstoffes als auch dessen Beschichtung einen Einfluss auf das tribologische Verhalten haben. Die Ergebnisse wurden in Form eines Reibzahlmodells konsolidiert und als mathematische Gleichung zur Verfügung gestel